Drain detection on the mos transistor with built-in channel - Верига, Андрій Дмитрович; Політанський, Леонід Францевич (Eastern-European Journal of Enterprise Technologies, 2012)
Modes of the drain detection in an autodyne sensor on the depletion MOS field-effect transistor are investigated. The analytical description of drain current dependence taking into account a load resistance in a drain circuit is carried out